Masticatory performance with different types of rehabilitation of the edentulous mandible - Flávio Domingues Neves; Tânia de Freitas Borges; Tânia de Freitas Borges; Daniela Baccelli Silveira Mendonça; Marisa Martins da Silva Prado; Karla Zancopé (Universidade Estadual de Campinas, 2015)
Aim: To compare the masticatory performance associated with different rehabilitation strategies for patients with edentulous mandibles. Methods: one portion of the test food "Optocal" was provided to groups: Natural Dentition (n = 15), Mandibular Fixed Implant-Supported Prosthesis with Maxillary Fixed Prosthesis (n = 8), Mandibular Fixed Implant-Supported Prosthesis with Maxillary Removable Prosthesis (n = 14), Mandibular Implant-Retained Overdenture with Maxillary Removable Prosthesis (n = 16), and Complete Dentures (n = 16). The portion was collected after 40 chewing strokes, and then passed through a stack of eight sieves with decreasing apertures. Masticatory performance was determined by weighing the portion of food on each sieve. Results: the masticatory performance was: 71.00% for Natural Dentition, 41.57% for Mandibular Fixed Implant-Supported Prosthesis with Maxillary Fixed Prosthesis, 31.44% for Mandibular Fixed Implant-Supported Prosthesis with Maxillary Removable Prosthesis, 27.70% for Mandibular Implant-retained Overdenture, and 14.33% for Complete Dentures. The data were statistically compared using Student's t-test (p < 0.05). Natural Dentition and Complete Denture groups were statistically different from all other groups, with the Natural Dentition and Complete Denture groups exhibiting the highest and lowest masticatory performance values, respectively. Conclusions: Osseointegrated implants improved the masticatory performance of all implant-supported groups compared to the Complete Dentures group.